PEMANFAATAN MODEL TAKSONOMI STRUCTURE OF THE OBSERVED LEARNING OUTCOME (SOLO) DALAM PENGEMBANGAN PERANGKAT EVALUASI PADA KOMPETENSI MENULIS SISWA SMP - Fahrudin Eko Hardiyanto (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
This  research  discussed the  development  of  evaluation  device using  the  SOLO  taxonomy, ranking  in  unistrucural  level  assessment  form,  multi-structural,  relational,  and  abstract. Statements of  the  problems in  this  study  were  1)  how  the  characteristics  of  the  taxonomic structure  of  the  evaluation  of  Observed  Learning  Outcome  (SOLO)  in  writing  competence,  2) how the principles  of  evaluation device development,  3)  how is evaluation device  draft, and 4) how  the  effectiveness  of  the  evaluation  device.  This  study  used  a  model of  Research  and Development (R  &  D),  which  is  the  research  and  development  of  the  writing  evaluation competency device of Junior Class VII with the subject of research were students and teachers in the  Junior  Class  VII  in  Pekalongan.  The  results  of  this  study  were  1)  Characteristics  of  the evaluation  based  on  the  SOLO  taxonomy writing  competence junior  school VII grade students based on the results of questionnaires from 40 respondents and the corresponding perception of teachers  based  on  the  results  of  questionnaires  of  4  respondents,  2)  the  development  of  the Principles evaluation based on SOLO taxonomy writing competence junior class VII include (a) the  principle  of  the  development  of  a  appropriate type  of  question  (b)  the  principle  of development  of multiple  choice  questions  (c)  the  principle  of  the  development  of  the  essay question  (d)  principles  for  the  development  of  question  type for critical  thinking  skills  (e)  the principle of development types of question for solving the problem ability, 3) Evaluation device draft based on SOLO taxonomy literary reading competence of VII grade of junior school in the form of conceptual material, lesson plans samples, evaluation grid, the card question, package of question completed with instructions, the answer key and scoring and 4) The evaluation is based on  SOLO  taxonomy  effective  reading  competence literary  views  of  validity,  reliabilities,  index of  level  of  difficulty,  and  the  distinguishing  features  about. The  question package  which  was examined  was as  many  as 10  trials  contained  eight  valid  questions.  Numbers/  scores  on  the evaluation  of  reliability  is  reached  about  1.786  with  categories  tested  reliable.  In  the  aspect  of difficulty  index  obtained  data  from  10  about  3  question  items  was the  excellent  category,  two items about both categories, with category 3 question items was enough, and one qustion items was  bad category.  While  on  the aspects  of  the  different  power, from  10  question items has  3 excellent, 3 questions were enough, and one question item was bad category.Keywords: SOLO taxonomy, development, evaluation device